The Effect Of Augmented Reality Interactive Learning Media For Vocational Students On Incresing Knowledge And Skills - Ahmad, Mardiana; Wabula, Popi; Syarif , Syafruddin; Handayani Idrus, Hasta (Journal of Neonatal Surgery, 2025)
Objectives: Improving vocational students' knowledge and skills in learning using Augmented Reality (AR) interactive learning media. Method: This research method is a literature review approach based on national and international scientific journals related to the use of Augmented Reality interactive technology to increase the knowledge and skills of vocational students. The literature reviewed and selected from several databases, namely PubMed, Scilit, ScienceDirect, Google Scholar and Semantic Sholar databases published from 2019 to 2024. This literature review was compiled by searching for scientific articles with the keywords 'increasing knowledge and skills, vocational students, Augmented Reality interactive learning media'. After filtering publications between 2019-2024, 115 articles were found, 30 articles were selected based on abstract, full text, open access, and eligibility. Finally, the authors read and selected the articles and obtained 30 relevant articles based on the specified criteria. Results: Augmented Reality (AR) Interactive learning media increases the knowledge and skills of vocational students, besides that AR also increases the effectiveness and quality of learning, students are more active in participating in learning so as to make learning more interesting and interactive. Conclusion: The use of Augmented Reality technology as an interactive learning medium is proven to be effective in improving vocational students' knowledge and skills. This literature review shows that AR not only improves conceptual understanding but also practical skills through a more immersive and interactive learning experience